Advanced echocardiography in neonates of diabetic mothers: a large population study of newborns. (25th November 2020) - Paerregaard, S; Voegg, R.O.B; Pihl, C.A; Bundgaard, H; Iversen, K.K
Abstract: Background: Maternal diabetes is associated with increased risk of congenital heart defects in the newborn, but the impact on systolic and diastolic function is less well described and findings are conflicting. Purpose: To assess subclinical cardiac abnormalities in newborns of diabetic mothers using advanced echocardiography. Methods: Transthoracic echocardiography (TTE) was performed within 30 days after birth in unselected neonates consecutively included in a prospective, multicenter, population-based study (2016–2018 (n=25, 750)). Cardiac function in newborns of mothers with pre-gestational (pre-GDM) or gestational diabetes (GDM) and a group of matched controls of newborns of non-diabetic mothers was assessed by Tissue Doppler Imaging (TDI) and Speckle Tracking Echocardiography (STE) to detect myocardial abnormalities. Controls were matched 1:1 by the following criteria; multiple pregnancy, sex, gestational age (± five days), age at TTE (± three days) and weight (± 200 g). Results: TDI and STE was performed in 317 newborns exposed to maternal diabetes during pregnancy (98 newborns of mothers with pre-GDM (females; 45.7%) and 219 newborns of mothers with GDM (females; 50%)). The mean age at time of TTE in newborns of diabetic mothers was 12 days (± 7 days). Cardiac function assessed with TDI showed significantly lower mitral valve (MV) systolic annular velocity (MV S') (3.15 cm/sec ± 0.67 vs 3.41 cm/sec ± 0.68, p=0.001), MV early diastolic annular velocity (MV E') (−4.71 cm/sec ± 1.26 vs −5.07 cm/sec ± 1.10, p=0.009), MV late diastolic annular velocity (MV A') (−4.24 cm/sec ± 1.25 vs −4.67 cm/sec ± 1.34, p=0.007) and interventricular septum late diastolic velocity (IVS A') (−4.49 cm/sec ± 0.89 vs −4.84 cm/sec ± 1.01, p=0.005) in newborns of mothers with pre-GDM compared to newborns of non-diabetic mothers. Newborns of mothers with GDM showed significantly lower MV A' (−4.35 cm/sec ± 1.35 vs −4.67 cm/sec ± 1.34, p=0.008) compared to newborns of non-diabetic mothers. When comparing subtypes of diabetes, newborns of mothers with pre-GDM had significantly lower MV E' (−4.71 cm/sec ± 1.26 vs −5.02 cm/sec ± 1.22, p=0.046) and IVS A' (−4.49 cm/sec ± 0.89 vs −4.75 cm/sec ± 0.93, p=0.033) compared to newborns of mothers with GDM. STE analysis showed that end-systolic and peak longitudinal strain (LS) were significantly lower in both subtypes of diabetes when compared to newborns of non-diabetic mothers; pre-GDM: end-systolic LS −17.93% and peak LS −19.18%, GDM: end-systolic LS −18.39% and peak LS −19.56% vs −19.56% and −20.29% in children of non-diabetic mothers, p<0.001 for all. Standard echocardiographic parameters were similar when comparing each subtype of diabetes with the newborns of non-diabetic mothers. Conclusion: Advanced echocardiography showed impaired systolic and diastolic cardiac function in newborns of diabetic mothers. The most severe impairment was seen in newborns of mothers with pre-gestational diabetes. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): PRIVATE COMPANY, Novo Nordisk Foundation: Pre-graduate Scholarhips 2019 - 6 months scholarship. Public Hospital, Herlev-Gentofte Internal Research Foundation 2019 - 6 months scholarship